Effect of carbon nanotubes on the biodegradability of poly(3‐hydroxybutyrate‐co‐3‐hydroxyvalerate) nanocomposites. Issue 40 (29th May 2019) - da Silva, Ana Paula; do Amaral Montanheiro, Thaís Larissa; Stieven Montagna, Larissa; Andrade, Patrícia Fernanda; Durán, Nelson; Lemes, Ana Paula
ABSTRACT: In this work, the effect of carbon nanotubes (CNT) on the biodegradability of poly(3‐hydroxybutyrate‐ co ‐3‐hydroxyvalerate) (PHBV) nanocomposites with 1 and 2% (w/w) of CNT has been evaluated by biodegradation assays in aqueous medium containing microorganisms extracted from garden soil. After biodegradation process, samples of PHBV and PHBV/CNT were compared regarding magnitude of degradation by visual macroscopic analysis, by measurement of percentage of weight loss and by scanning electron microscopy (SEM). The samples were further characterized regarding roughness and hydrophilicity by contact angle measurement. The final residue resultant from biodegradation of PHBV/CNT was analyzed in a FEI Inspect F50 field emission scanning electron microscope (FESEM) in order to verify the presence of CNT. Our results indicated that CNT did not compromise the biodegradability of PHBV matrix although the biodegradation rate has decreased with the increase of CNT content as shown by the weight loss measurements. SEM analysis of PHBV/CNT nanocomposites after biodegradation process showed increased amount of CNT exposed at the matrix surface suggesting the possibility of CNT recovering after the biodegradation. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 48020. Abstract : Analysis of the biodegradation of a new material and its residue is essential to trace the most appropriate way to discard it according with the principles of sustainability.